Photocatalytic Degradation of E.Coli Bacteria by Graphitic Carbon Nitride Photocatalysts under Visible Light Irradiation - Zahra Ahmadi Panah; Reyhaneh Dehghan; Mehran Bijari; Afsaneh Shahbazi (آب و فاضلاب)
Photocatalytic technology offers novel solutions for wastewater treatment using visible light. Graphitic carbon nitride, as a polymeric semiconductor, has attracted significant attention in this field. However, overcoming the limitations of this material remains a major challenge for researchers. In this study, a graphitic carbon nitride photocatalyst was synthesized using a thermal polymerization method with melamine as a precursor in a new gaseous atmosphere of CO2. For comparison, similar samples were synthesized in common atmospheres such as N2 and air. The structure, morphology, and properties of the samples were characterized using various analyses. Additionally, considering the importance of E.Coli bacteria, their antibacterial activity against this bacterium was evaluated under both light and dark conditions. The sample synthesized in the CO2 atmosphere had a surface area approximately 3 and 2 times higher than those synthesized in air and nitrogen atmospheres, respectively. Also, the luminescence intensity of this sample was significantly lower, indicating an improvement in photocatalytic performance. The results of microbiological tests showed that the CN-CO2 sample completely inactivated E.Coli bacteria with an initial concentration of 107 CFU/mL when exposed to an effective dose of 0.2 g/L within 180 minutes under visible light irradiation. In contrast, the CN-air and CN-N2 samples inhibited 62.7% and 29.5% of the bacteria, respectively. The results also indicated that CN-CO2 had a high ability to inhibit bacterial growth in the dark. The results of the disk diffusion assay and bacterial viability tests in solid media also confirmed these findings. Given the significant advantages of this nanomaterial (CN-CO2), including high photocatalytic activity, strong antibacterial properties, and a simple and one-step synthesis method, it can be used as an efficient photocatalyst for water and wastewater treatment industries.